Constitutional development among the Voortrekkers, 1836-56 (Historia, 2021)
The  nineteenth century  saw  a  considerable expansion ~f  Europeansettlement in  Australasia, southern Mrica   and  North  America.   All   areof  great interest politically,  socially and  economically, but  for  the  studentof  constitutional development the southern Mrican  movement is of  possiblyunique  interest.   The  American,  the  Australian  or  the  New  Zealandertook  his  accepted constitutional forms  and  practices  with  him,  but  theVoortrekkers left  in  search of  independence, seeking escape from  politicalpractices and  theories of  which  they disapprovea.   In  other words  thoseother pioneers advanced their  frontiers, while  the Trekkers broke  throughtheir's,  intent  on  preserving the  old  ways on the  other side.   They there-fore  had  to  erect  their  own  constitutional  establishments, starting  verynearly    from  scratch as  far  as  the  central  government was  concerned,though they were better placed as regards local  government, having  hadsome first  hand  experience of  the  Cape's system.   It   is  in  the  uniquenature of their  movement and the fact that they were not over well equippedfor  their  self imposed task that the major  interest in  studying their  actionslies
Keywords: Constitution; Voortrekkers; Orange Free State